The effect of social economic status towards academic achievement of form four students in Perlis - Noorfauziah, Mustaffa (2014)
Educational sector is an important agenda for any country. A country may develop according to how the educational sector planned. Therefore the purpose of this study is to determine the effects of Social Economic Status (SES) towards Academic Achievement (AA). This study was conducted on 267 respondents who are students from three secondary schools which are from three different zones in Perlis. The scopes of Socio Economic background of family include in the study are the family income, parents’ education level and parents’ occupation. Meanwhile the academic achievement refers to the students’ achievement in their PMR. The adaption of instruments in this research is based on the constructs in the structured model illustrated in and to run the analysis simultaneously, the study data been analysed using the structured equation model. The magnitude of estimation of direct effect among construct also been conducted. The result of this study shows there is a significant direct effect of parent’s income to the student’s academic achievements. However the study shows that the parent’s educational level and parent’s occupation status do not have significant direct impact to the student’s academic achievement. These findings suggest that a better planning or programme for students from low income family group is needed in order to uplift the student’s achievement. A better planning or programme hopefully, will close the gap of academic achievement between the student’s from low and higher income group.